Second Five Year Plan Approach and Organisation - Planning Commission (Planning Commission, 1956)
This Report sets out the proposals of the Planning Commission for the Second Five Year Plan. The Plan was considered in draft by the National Development Council which passed the following Resolution on the 2nd May, 1956: “Having considered the Draft Second Five Year Plan, “The National Development Council places on record its general approval and acceptance of the objectives, priorities and programmes embodied in the Plan; and “Relying on the enthusiasm and support of the people
Government of India Planning Commission